Software quality assurance - Laporte, Claude Y.; April, Alain 1958- (Wiley-IEEE Computer Society, Inc., 2018)
"This book introduces Software Quality Assurance (SQA) and provides an overview of standards used to implement SQA. It defines ways to assess the effectiveness of how one approaches software quality across key industry sectors such as telecommunications, transport, defense, and aerospace"--
Includes bibliographical references and index. - Print version record and CIP data provided by publisher
Keywords: Computer software -- Quality control; Computer software -- Quality control -- Standards; Logiciels; Qualité; Contrôle; TECHNOLOGY & ENGINEERING; Quality Control; Computer software; Quality control; Computer software; Quality control; Standards